From Data Islands to Sharing Data in the Cloud: the Evolution of Data Integration in Biological Data Repositories - Cogo, Vinicius Vielmo; Bessani, Alysson Neves (Revista ComInG - Communications and Innovations Gazette, 2016)
Biological data repositories were often data islands with unharmo- nized formats, models, and protocols. Their integration evolved along the years and sharing data in multi-tenant infrastructures is a reality now. In this article, we illustrate this evolution by presenting real-world cases from the bioinformat- ics area and collect the best practices and current trends that future solutions should observe from these examples. Finally, we situate the platform being cre- ated by the BiobankCloud project in the scenario of integrating biological data.